An Analysis of Digital Technology Impact on Improving the Environmental Status - Victoria Ilchenko, Vladislava Bondarenko, Oksana Koroliova, Svitlana Petrovska (International Journal of Advanced Science and Technology, 2020)
The basic lines of the modern state of environment economic district of Ukraine are certain. The article studies the nature of the regional innovation system, its place in the regulation process of greening the region through improving the mechanism of implementing environmental innovations. Influences of basic pollutants and types of anthropogenic loading on the environment of the region are described. The article analyzes the current state of innovation and innovative activity of industrial enterprises, making it possible to identify the main problems and obstacles implementing key ecological digitalization. It is established that the policy of funding innovative industrial activities is a major problem. Also, public administration is in critical condition about the ability of regulatory innovation in the field of nature, is imperfect institutional support, infrastructure needs improvement. The modern state of the secondary use and treatment of natural resources in the region is described. The main directions of improvement of the governance process of greening the region. The territorial features of levels of contamination of atmospheric air, soils and waters are set. The specific of the ecological state in the municipal and rural locality, depending on the specialization of economic development of territory is certain. The analysis of reasons for morbidity and death rate of the population out depending on the development of the industry is carried. The basic problems of ecological character are distinguished and the ways of their decision are offered. An important step is also the implementation of policies aimed at protecting life and health from the negative effects caused by environmental pollution, achieving a harmonious interaction between society and nature.